2004
DOI: 10.1097/01.pas.0000126785.61609.6e
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative Nodules in Congenital Melanocytic Nevi

Abstract: Congenital melanocytic nevi (CMN) occur in 1% to 2% of newborns, and the risk of malignant melanoma is increased in patients with large CMN. Appearance at birth or later of a nodular or hyperpigmented area within a CMN simulates malignant melanoma and prompts biopsy. Although their clinical and pathologic features seem ominous, proliferative nodules (PNs) typically are benign and may regress, although atypical features cause greater concern. Here we report clinical and pathologic findings with outcome in 10 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(25 citation statements)
references
References 38 publications
2
21
2
Order By: Relevance
“…In agreement with our results, Rudolph et al 5 and Li et al 6 detected < 1% immunoreactivity in the junctional and upper dermal parts of congenital nevi. Other investigators have also found low Ki‐67 labeling only in a subset of congenital nevi examined 7 . Bergman et al 8 found a marked reduction of Ki‐67 staining in the dermal component of ordinary melanocytic nevi in contrast to melanomas, which displayed only a slight and insignificant decrease.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In agreement with our results, Rudolph et al 5 and Li et al 6 detected < 1% immunoreactivity in the junctional and upper dermal parts of congenital nevi. Other investigators have also found low Ki‐67 labeling only in a subset of congenital nevi examined 7 . Bergman et al 8 found a marked reduction of Ki‐67 staining in the dermal component of ordinary melanocytic nevi in contrast to melanomas, which displayed only a slight and insignificant decrease.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, they observed only rare (< 5%) reactivity in all melanomas. Herron et al 7 found p‐53 staining ranging from < 10% to > 50% in 9 of 30 (30%) specimens of congenital nevi. The increased detection of p‐53 in the study of Herron et al 7 may be explained by the selected sample, which included only congenital nevi with atypical proliferative nodules.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although high and broad expression has been observed by other investigators in various types of nevi including Spitz nevi, 39,40 others have demonstrated lower rates of bcl-2 expression ranging from 23% to 40% in acquired and congenital nevi. 37,41 In conclusion the interesting subset of Spitz nevi differ from melanomas in their immunohistochemical pattern of expression and demonstrate a distinct pattern, which may help in the correct diagnosis.…”
Section: Discussionmentioning
confidence: 96%
“…40 The expression of c-kit was observed even in proliferative nodules which appear in CMN. 41 Although there are reports of familial cases of CMN, most of these lesions occur in at random. 7,42 …”
Section: Pathogenesismentioning
confidence: 99%